Administrative Office of Don Host Oblast, Nineteenth to Early Twentieth Centuries: Kalmyk Cossacks in Education-Related Ethnic Policy - Konstantin N. Maksimov (Oriental Studies)
Introduction. The article analyzes ethnic-specific educational policy adopted by the Tsarist Government and administrative bodies of Don Host Oblast towards Kalmyks Cossacks from the 1830s to the October Revolution. Goals. The paper shall step by step investigate the mentioned policy of imperial and Don Host agencies, describe how the network of educational institutions would unfold in Kalmyk and Salsky districts throughout the identified period. Materials and methods. The study rests on the principles of objectivity and historicism, employs tools of comparative analysis. It focuses on a variety of newly introduced archival materials and collections from Reference Books of Don Host Oblast for the years 1885–1915. Results. The work provides a historical review of the educational system across Kalmyk-inhabited stanitsas: the year 1839 was marked by the opening of Kalmyk Congregational School, and by the early twentieth century there were a number of institutions (including female ones) in virtually all stanitsas and most khutors of Salsky District. Furthermore, Kalmyk children would attend other public-funded educational organizations of Don Host Oblast, such as Military and Vocational School, railroad and non-classical colleges, gymnasiums. The paper pays particular attention to the teaching staff and literacy evaluations among children of Kalmyk Cossacks. Conclusions. The Don Host administrative office did join efforts with Buddhist clerics, Ministry of War, and Ministry of Public Education to develop a network of educational institutions in Kalmyk settlements and enhance literacy among Kalmyk Cossacks. This served a key adaptation factor for ethnic Kalmyks within the Don Host and its community.